UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK MELALUI PENGGUNAAN METODE FONIK TERPADU DI KELAS 1 SD UPTD INPRES SIKUMANA 3 - Aziza, Wafiq; Ande, Andreas; Sampe, Markus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is entitled "Efforts to Improve Students' Early Reading Skills Through the Use of Integrated Phonics Methods in Grade 1 of Elementary School UPTD SD Inpres Sikumana 3". This study is motivated by the low initial reading skills of grade 1 students of elementary school UPTD SD Inpres Sikumana 3 Kupang City in the 2025/2026 academic year. This study aims to improve the initial reading skills of grade 1 students of elementary school UPTD SD Inpres Sikumana 3 Kupang through the application of integrated phonics methods in the form of two-cycle Classroom Action Research (CAR). The subjects of the study were 28 grade 1 students who experienced early reading difficulties, with a pre-cycle completion rate of only 29% and an average score of 4.71. The results of cycle I showed a completion rate of 64% (average score of 7.5) and cycle II reached 89.28% (average score of 9.28), exceeding the target of 80%. Based on the results of this study, it can be concluded that the integrated phonics method is effective in improving early reading skills quantitatively and qualitatively in grade 1 elementary school students at UPTD SD Inpres Sikumana 3. This study is recommended to be widely applied in early literacy learning in elementary schools.